UJI HIDUP DIPERCEPAT PADA DISTRIBUSI EKSPONENSIAL TERSENSOR TIPE II DENGAN TEGANGAN KONSTAN - Prayudhani, Oktaviana; Wuryandari, Triastuti (MEDIA STATISTIKA, 2010)
Accelerated Life Testing (ALT) is used to obtain information quickly on life distribution, failure rates and reliabilities. ALT is achieved by subjecting the test units to conditions such that the failure occur sooner. Prediction of long term reliability can make within a short periode of time. Result from the ALT are used to extrapolate the unit characteristic at any future time and at given normal operating conditions. ALT using a time varying stess application is often used to induce failure in relatively short times. The most basic and useful type of ALT in which the stress on each unit is increased step by step over time, it can substantially shorten the duration of the reliability test. The life distribution which used in reliability test is exponential distribution. By using Maximum Likelihood Estimation is obtained point estimation of parameter on step stress, and povital quantity is obtained confidence interval for parameter. From this estimation Mean Time to Failure (MTTF) and reliability of product under normal operating condition Â  Keysword: Accelerated Life Testing (ALT), Step Stress, Exponential Distribution, Maximum Likelihood Estimation, Povital Quantity